2002
DOI: 10.3310/hta6350
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the costs and effectiveness of different models of paediatric home care

Abstract: et al. A systematic review of the costs and effectiveness of different models of paediatric home care. Health Technol Assess 2002;6(35). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see opposite). NHS R&D HTA Programme T he NHS R&D Health Technology Assessment (HTA) Programme was set up in 1993 to ensure that high-quality research information on the costs, effectiveness and broader impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 85 publications
(291 reference statements)
1
31
0
1
Order By: Relevance
“…International research has shown that CCTH services vary, but that they can be broadly classified by focus, location and timing of input (Parker et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…International research has shown that CCTH services vary, but that they can be broadly classified by focus, location and timing of input (Parker et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric home care (PHC) facilitates continuation of a normal life for children and their families by reducing disruptions resulting from hospital admissions. Accordingly, provision of PHC for children with cancer, as well as for children with other acute and chronic illnesses, is increasing because of technological developments, improvements in the understanding of factors for complications, the costs of hospital‐based health care, changing policies, and the potential psychosocial advantages 5–8. There is no consensus on the definition of PHC, but PHC is in general either a community‐based service that primarily supports children with long‐term conditions, or a hospital‐based service that provides specialist care such as cancer treatment 9.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing provision of PHC in general, three systematic reviews of PHC have found that controlled studies are rare and that the evidence base is limited 5, 7, 9. Knowledge is sparse about the effect of PHC on the frequency of hospital admissions, length of hospital stays, children's health outcomes and quality of life (QOL), and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric home care (PHC) facilitates the continuation of normal life for children and their families and is on the increase due to the potential psychosocial benefits of home care and the costs of hospital-based health care [17]. There is no consensus on the definition of PHC and the service can be based on both general and specialist schemes.…”
Section: Introductionmentioning
confidence: 99%
“…General PHC services most often work from a community base in a single district. By contrast, specialist services are more likely to be hospital-based, providing service to more than one district [17-20]. Outpatient treatment is provided by health care professionals in the outpatient clinic at the hospital while PHC provides treatment by health care professionals in the child’s home.…”
Section: Introductionmentioning
confidence: 99%